Stereotactic Radiotherapy for Pulmonary Oligometastases From Colorectal Cancer: A Systematic Review and Meta-Analysis. (20th August 2018) - Jingu, Keiichi; Matsushita, Haruo; Yamamoto, Takaya; Umezawa, Rei; Ishikawa, Yojiro; Takahashi, Noriyoshi; Katagiri, Yu; Takeda, Kazuya; Kadoya, Noriyuki
Purpose: The purpose of this study was to determine whether pulmonary oligometastases from colorectal cancer have greater radioresistance than that of pulmonary oligometastases from other cancers and whether good local control can be achieved by dose escalation in stereotactic body radiotherapy. Materials and Methods: This systematic review and meta-analysis were conducted according to the preferred reporting items for systematic reviews and meta-analyses statement and methods. Studies were obtained from a database search of PubMed, Web of Science, and Google Scholar for publications using search terms designed to identify studies on "oligometastases, " "lung, " "stereotactic radiotherapy, " and "colorectal cancer." For meta-analysis 1, studies that showed the number of local failures after stereotactic body radiotherapy for pulmonary metastases from colorectal carcinoma and other cancers were included. For meta-analysis2, studies in which a comparison was made of local control rates of pulmonary metastases from colorectal carcinoma by stereotactic body radiotherapy with a higher dose and that with a lower dose were included. A meta-analysis was performed using Mantel-Haenszel statics with the fixed or random-effect model by Review Manager 5.3. Results: Eighteen retrospective studies with 1920 patients with pulmonary oligometastases were used in meta-analysis 1. The local control rate in patients with pulmonary oligometastases from colorectal cancer was significantly lower than that in patients with pulmonary oligometastases from other cancers (odds ratio = 3.10, P < .00001). Next, 8 retrospective studies with 478 patients were included in meta-analysis 2 for dose escalation. Better local control was achieved by a higher prescription dose than by a lower prescription dose (odds ratio = 0.16, P < .00001). Conclusion: Our meta-analysis indicated that local control of pulmonary oligometastases from colorectal cancer by stereotactic body radiotherapy was significantly worse than that of pulmonary metastases from other cancers; however, our results also indicated that good local control of pulmonary oligometastases from colorectal cancer can be achieved by dose escalation.